2012
DOI: 10.1002/etc.1935
|View full text |Cite
|
Sign up to set email alerts
|

Use of solid phase microextraction to estimate toxicity: Relating fiber concentrations to toxicity—part I

Abstract: Use of solid-phase microextraction (SPME) fibers as a dose metric for toxicity testing was evaluated for hydrophobic pesticides to the midge Chironomus dilutus and the amphipod Hyalella azteca. Test compounds included p,p'-dichlorodiphenyltrichloroethane (p,p'-DDT), p,p'-dichlorodiphenyldichloroethane (p,p'-DDD), p,p'-dichlorodiphenyldichloroethylene (p,p'-DDE), permethrin, bifenthrin, tefluthrin, and chlorpyrifos. Acute water toxicity tests were determined for 4- and 10-d exposures in both species. Median let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 47 publications
(98 reference statements)
1
35
1
Order By: Relevance
“…The difference in chlorpyrifos toxicity is likely caused by a different experimental setup, asPhipps et al (1995) used a flow-through system, whileDeanovic et al (2013) andBrand- er et al (2009) used a static system as was used in this study. No 10-day LC 50 was reported for C. dilutus in the literature for cyfluthrin, and values reported for the other three chemicals differed from the ones determined in this study Ding et al (2012). determined different LC 50 of bifenthrin (23.0 ng/L), permethrin (99.0 ng/L), and chlorpyrifos (140.0 ng/L) for C. dilutus using a static system, without solution renewal and a decreased feeding interval, which possibly caused the differing values compared to this study.…”
contrasting
confidence: 83%
“…The difference in chlorpyrifos toxicity is likely caused by a different experimental setup, asPhipps et al (1995) used a flow-through system, whileDeanovic et al (2013) andBrand- er et al (2009) used a static system as was used in this study. No 10-day LC 50 was reported for C. dilutus in the literature for cyfluthrin, and values reported for the other three chemicals differed from the ones determined in this study Ding et al (2012). determined different LC 50 of bifenthrin (23.0 ng/L), permethrin (99.0 ng/L), and chlorpyrifos (140.0 ng/L) for C. dilutus using a static system, without solution renewal and a decreased feeding interval, which possibly caused the differing values compared to this study.…”
contrasting
confidence: 83%
“…For such applications, the use of SPME has been shown to be superior to others technique due to the resulting lack of cell damage that ensues from pipetting or centrifugation, as well as the circumvention of trypsinization [31]. In other work, SPME-based toxicity studies of hydrophobic pesticides in water have been reported by Ding et al [32,33]. Although assessing environmental risk rather than organ-specific toxicity, a few important features of SPME as they relate to toxicity are well emphasized in this work.…”
Section: Cytotoxicitymentioning
confidence: 95%
“…Both the equilibrium fiber concentrations (C f ) and the LC50 and median effective concentration (EC50) values on a fiber concentration basis were determined in our companion paper [13].…”
Section: Solid Phase Microextraction and Fiber-based Median Lethal Comentioning
confidence: 99%
“…In most of these studies, bioaccumulation was measured at sublethal levels. Whereas a conceptual model supported the theory that a relationship would be expected between SPME concentrations at equilibrium and toxic responses [13], a more complete explanation linking SPME fibers concentrations and toxicity response was impor-tant for future reliance on this approach. Fewer studies have linked SPME fiber concentrations to body residues at lethal levels or linked SPME fibers to the subsequent toxic effects [1,[11][12][13].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation